Pengaruh Trimetazidine Terhadap Jumlah Netrofil Pasca IKPP - Taka Mehi; Yoga Yuniadi; Nur Haryono (Jurnal Kardiologi Indonesia, 2015)
Background: Reperfusion strategy, either with thrombolytic or Primary Percutaneous Coronary Intervention (PPCI), is the core treatment for Acute ST-Segment Elevation Myocardial Infarct (STEMI). The goal of PPCI is to restore the patency of infarcted epicardial artery and establish microvascular reperfusion as soon as possible so that necrotic myocardial area can be reduced. However, successful restoration of infarcted epicardial artery is not always followed by enough reperfusion to the microvascular part. Trimetazidine can reduce neutrophil which was mediated by tissue trauma during ischemic heart condition. Unfortunately, its influence over neutrophil accumulation in acute STEMI patients which undergo PPCI is not well understood.Method: There were 68 consecutive-selected acute STEMI patients which undergo PPCI since January 2015 until Juni 2015. They were admitted in emergency department. Peripheral vein blood sampling was taken to measure neutrophil before PPCI was performed. Six hour after PPCI was conducted, another peripheral vein blood sampling was taken for another neutrophil measurement. Neutrophil measurement was performed with Sysmex 2000i. Statistical analysis was performed by using SPSS 17.Result: Among 68 patients, divided in two groups, trimetazidine 28 patients and plasebo 40 patients. There were no differences amount of neutrophils in trimetazidine or plasebo group, before or after PPCI. Neutrophil pre PPCI in trimetazidine vs plasebo group 10.71 ± 3.263 vs 10.99 ± 3.083, p:0,341. Neutrophil post PPCI in trimetazidine vs plasebo group 9.49 ± 3.135 vs 9.92 ± 3.463, p:0,664.Conclusion: There were no reducing amount of neutrophils after trimetazidine was given in patients STEMI which underwent PPCI